A community mobilization intervention to improve engagement in HIV testing, linkage to care, and retention in care in South Africa: a cluster-randomized controlled trial - Sheri A. Lippman; Audrey Pettifor; Mi-Suk Kang Dufour; Chodziwadziwa Whiteson Kabudula; Rhian Twine; Dean Peacock; Rhandzekile Mathebula; Aimée Julien; Rebecca West; Torsten B. Neilands; Ryan Wagner; Ann Gottert; et al. (My University, 2022)
Background: Community Mobilization (CM), engaging communities in a process to collectively enact change, could improve HIV testing and care engagement. We assessed whether CM increased HIV testing, linkage to, and retention in care over time in intervention relative to control communities. Methods: Fifteen communities in Mpumalanga, South Africa were randomized to either a CM intervention engaging residents to address social barriers to HIV testing and treatment or to control. Implementation occurred from August 2015-July 2018. Outcomes included quarterly rates of HIV testing, linkage to care, and retention in care documented from health facility records among 18-49 year-old residents of intervention and control communities over the three years of study. Intention-to-treat analyses employed generalized estimating equations stratified by sex. ClinicalTrials.gov number NCT02197793. Findings: Residents in eight intervention communities (N=20,544) and seven control communities (N=17,848) contributed data. Among men, HIV testing increased quarterly by 12·1% (Relative Change (RC):1·121, 95%CI:1·099-1·143) in intervention communities and 9·5% (RC:1·095, 95%CI:1·075-1·114) in control communities; differences by arm were marginally significant (exponentiated interaction coefficient:1·024, 95%CI:0·997-1·052, p-value=0·078). Among women, HIV testing increased quarterly by 10·6% (RC:1·106, 95%CI:1·097-1·114) in intervention and 9·3% (RC:1·093, 95%CI:1·084-1·102) in control communities; increases were greater in intervention communities (exponentiated interaction coefficient:1·012, 95%CI:1·001-1·023, p-value=0·043). Quarterly linkage increased significantly among intervention community women (RC:1·013, 95%CI:1·002-1·023) only. Quarterly retention fell among women in both arms; however, reductions were tempered among intervention women (exponentiated interaction coefficient:1·003, 95%CI:<1·000-1·006, p-value=0·062). No significant differences were detected in linkage or retention among men. Interpretation: CM was associated with modest improvements in select trial outcomes. The sum of these incremental, quarterly improvements achieved by addressing social barriers to HIV care engagement can impact epidemic control. However, achieving optimal impacts will likely require integrated efforts addressing both social barriers through CM and provision of improved service delivery.